To the phase dynamics of relativistic electron bunches at plasma wakefield excitation - Onishchenko, I.N.; Maslov, V.I. (Вопросы атомной науки и техники, 2009)
Theoretical investigation of influence of radial component of plasma wakefield on phase dynamics of the bunches has
been performed. The wakefield is excited in plasma by long sequence of the relativistic electron bunches. It has been
shown that at certain conditions this radial wakefield leads to more quick shift of the bunches, in comparison with
shift by longitudinal wakefield, from decelerating phases into accelerating phases. This shift leads to change of a sign
of an energy exchange of electron with a wave and to plasma wakefield amplitude saturation. Проведено теоретичне дослiдження впливу радiальної компоненти поля кiльватерної хвилi на фазову
динамiку згусткiв. Кiльватерна хвиля збуджується у плазмi довгою послiдовнiстю релятивiстських
електронних згусткiв. Показано, що при визначених умовах ця радiальна компонента приводить до
бiльш швидкого ссуву згусткiв, порiвняно з ссувом пiд дiєю повздовжньої компоненти, iз гальмуючих
фаз в прискорюючi. Такий ссув призводить до змiни знаку енергообмiну згусткiв з хвилею i до насичення її амплiтуди. Проведено теоретическое исследование влияния радиальной компоненты поля кильватерной волны на
фазовую динамику сгустков. Кильватерная волна возбуждается в плазме длинной последовательностью релятивистских электронных сгустков. Показано, что при определенных условиях эта радиальная
компонента приводит к более быстрому смещению сгустков, чем под действием продольной компонен-
ты, из тормозящих фаз в ускоряющие. Такое смещение приводит к смене знака энергообмена сгустков
с волной и к насыщению ее амплитуды.